2023
DOI: 10.1038/s41598-023-39140-3
|View full text |Cite
|
Sign up to set email alerts
|

PermaNet Dual, a new deltamethrin-chlorfenapyr mixture net, shows improved efficacy against pyrethroid-resistant Anopheles gambiae sensu lato in southern Benin

Abstract: Pyrethroid-chlorfenapyr nets have demonstrated improved entomological and epidemiological impact in trials across Africa. This is driving increased demand for this novel net class in malaria-endemic countries. PermaNet Dual is a new deltamethrin-chlorfenapyr net developed by Vestergaard Sàrl to provide more options to malaria control programmes. We performed an experimental hut trial to evaluate the efficacy of PermaNet Dual against wild, free-flying pyrethroid-resistant Anopheles gambiae sensu lato in Covè, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
6
4
0
Order By: Relevance
“…In laboratory studies, the ability of an ITN to remain effective over several years is assessed by subjecting nets to bioassays and chemical analysis for up to 20 standardised washes – a surrogate for insecticidal loss over 3 years of field use assuming nets are washed every few months (19). Both pyrethroid-CFP ITNs met WHO efficacy thresholds in tunnel tests after 20 washes corroborating previous studies (22, 30, 31) and thus showing their potential to remain efficacious over several years of household use. This suggests that the lower total CFP content retention observed with PermaNet® Dual compared to Interceptor® G2 had little or no impact on the durability of its insecticidal activity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In laboratory studies, the ability of an ITN to remain effective over several years is assessed by subjecting nets to bioassays and chemical analysis for up to 20 standardised washes – a surrogate for insecticidal loss over 3 years of field use assuming nets are washed every few months (19). Both pyrethroid-CFP ITNs met WHO efficacy thresholds in tunnel tests after 20 washes corroborating previous studies (22, 30, 31) and thus showing their potential to remain efficacious over several years of household use. This suggests that the lower total CFP content retention observed with PermaNet® Dual compared to Interceptor® G2 had little or no impact on the durability of its insecticidal activity.…”
Section: Discussionsupporting
confidence: 87%
“…Hence, the superior performance of PermaNet® Dual against the susceptible strain in cone bioassays was probably due to the higher loading dose and surface availability of pyrethroid in PermaNet® Dual rather than differences in the type of pyrethroid used on each net. The comparable performance of PermaNet® Dual and Interceptor® G2 against pyrethroid-resistant mosquitoes is consistent with a recent experimental hut trial in Benin which demonstrated the non-inferiority of PermaNet® Dual to Interceptor® G2 against wild, pyrethroid-resistant mosquitoes (30). Based on this and similar evidence of efficacy from trials in Côte d’Ivoire (31) and Kenya (22), PermaNet® Dual was added to the WHO list of prequalified vector control products (17) and included in the recent policy recommendation for pyrethroid-CFP ITNs (22).…”
Section: Discussionsupporting
confidence: 86%
“…funestus mosquitoes relative to the control in the experimental huts. PermaNet Dual induced the highest mortality rates which was not signi cantly different from Interceptor G2 but was signi cantly higher than PermaNet 3.0 at corroborating results from previous hut trials in Benin [32]. Similar observations have been made in experimental hut trials evaluating PermaNet Dual and Interceptor G2 where in each instance, the pyrethroid-chlorfenapyr LLIN induced higher mortality than the pyrethroid-PBO or pyrethroid only LLINs [23,32,33].…”
Section: Discussionsupporting
confidence: 86%
“…This shows the contribution of chlorfenapyr to the control of resistant mosquitoes where mechanisms other than P450 monooxygenases are active such as in this population. Similar ndings have been documented in Tanzania [10], where there was a higher impact on entomological outcomes in clusters with Interceptor G2 than those with PermaNet 3.0, and in another experimental hut trial evaluating the non-inferiority of PermaNet Dual to Interceptor G2 [32].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation